2017
DOI: 10.1103/physrevmaterials.1.065602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of hydrogen guests in ice XVII nanopores

Abstract: The present high-resolution inelastic neutron scattering experiment on ice XVII, containing molecular hydrogen with different ortho/para ratio, allows to assign the H2 motion spectral bands to rotational and center-of-mass translational transitions of either para-or ortho-H2. Due to its structure, ice XVII confines H2 molecules to move in spiral channels of molecular size. Reported data demonstrate that H2 molecules rotate almost freely in these nanometric channels, though showing larger perturbation than in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The experimental INS data can be compared with the simulated PDOS curves, because the INS measurements collected the phonon signals throughout the whole BZ [25]. A comparison of the INS data ( [26]) and calculated PDOS of deuterated ice XVII is shown in figure 2 to manifest the validity of the simulation in this work.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The experimental INS data can be compared with the simulated PDOS curves, because the INS measurements collected the phonon signals throughout the whole BZ [25]. A comparison of the INS data ( [26]) and calculated PDOS of deuterated ice XVII is shown in figure 2 to manifest the validity of the simulation in this work.…”
Section: Resultsmentioning
confidence: 72%
“…Thus, the physical mechanism of H-bonding in ices is best understood in terms of the local tetrahedral structure. In figure 3, two examples of normal modes at 209 and 301 cm −1 are [26] were measured using deuterated ice XVII, and the calculations were also performed using a 48-molecule model of deuterated ice XVII. illustrated, with a frequency ratio of 1.44.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 This low density solid water phase has the characteristic of being highly porous, and, unique among the various stable and metastable phases of ice, exhibits a structure comprising only pentagonal rings of water molecules. 15,16 Ice XVII can be maintained at room pressure only up to about 130 K, above which it undergoes a phase transition similar to that mentioned above for the amorphous 10 and high-pressure crystalline 11,12 forms. Whilst the end-product of all of these transitions, above 200 K, is the ordinary hexagonal form of ice (ice Ih), the remarkable difference between ice XVII and the other forms is the nature of the intermediate state, where, instead of stacking-disordered ice, we find a structurally-pure form of cubic ice (true ice Ic).The transition can be easily detected by Raman spectroscopy, which is also a valuable method to study the transition kinetics as a function of either temperature or time.…”
mentioning
confidence: 74%
“…Finally, Amos et al found that sX also exists in the carbon dioxide:water system and determined the full structure of both hydrogen and carbon dioxide hydrates in situ using neutron diffraction 15 . Due to the high guest-host ratio, the reversibility of the filling and emptying, and the Nitrogen sX Hydrate high mobility of hydrogen in the cavities, the sX/ice XVII system has been proposed as a possible hydrogen storage material 34,35 . Other possible applications, however, have not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen sX Hydrate As shown by del Rosso et al, guest molecules in the sX structure are highly mobile and are not locked into one position 34,35 . This results in a rather continuous nitrogen density along the helical channels.…”
mentioning
confidence: 99%